How UK companies use their codes of ethics – highlights of the 2007 Institute of Business Ethics survey. (20th February 2009) - Werner, Andrea; Webley, Simon
This paper reports on selected findings from the Institute of Business Ethics' fifth survey into how FTSE 350 companies use their codes of ethics. This is a triennial survey and the majority of the survey questions have been held consistent throughout the years, making possible the identification of changes in how companies approach making their code effective. This paper will focus on the following aspects: purpose and administration of the code, implementation and embedding, monitoring and revision, reference to external standards and guidelines, significant ethical issues and the extent to which ethics programmes take the issue of climate change into account. Differences between FTSE 100 and FTSE 250 listed companies will also be examined.